Photophysicochemical properties and surface-enhanced Raman scattering of phthalocyanine-nanoparticle conjugates - Nwahara, Nnamdi (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
This work presents the synthesis, photophysical and photochemical characterization of a series of metallophthalocyanines (MPcs) and boron dipyrromethene (BODIPY) and their conjugates with either gold or silver nanoparticles (AuNPs or AgNPs) or graphene quantum dots (GQDs). The rich Ï€-electron systems of GQDs and MPcs employed in this work enabled the coordination of MPcs to GQDs (either as pristine or modified) via the non-covalent (Ï€-Ï€ stacking) method. GQDs, AuNPs and AgNPs were also functionalized with L-glutathione (GSH) in order to assist coupling to the Pcs or BODIPY dye. Spectroscopic and microscopic studies confirmed the formation of the respective nanoparticles (NPs) as well as the conjugates which exhibited enhanced photophysicochemical properties in comparison to the phthalocyanines (Pcs) or BODIPY alone. This work also shows that the incorporation of folic acid (FA) into Pcs-NPs composites leads to further enhancements in the singlet oxygen generation capabilities of the resulting conjugates, and so experimentally demonstrates for the first time, a synergy between FA and the respective nanoparticles (GQDs, AuNPs and AgNPs) in affecting the photophysical properties of Pcs complexes. GQDs and Pcs/GQDs hybrids were also herein decorated with AuNPs "“ metallic nanostructures that employ localized surface plasmon resonances to capture or radiate electromagnetic waves at optical frequencies. These nanostructures herein reported, have been shown to possess enhanced light-matter properties, enabling unique surface-enhanced Raman scattering (SERS) behaviours, with unprecedented enhancement factors of up to 30-fold. This work therefore, reports on the fabrication of Pc/GQDs/AuNPs hybrids and experimentally demonstrates their incredible potential as novel Raman-active PDT agents.
Keywords: Boron compounds; Electrochemistry; Phthalocyanines; Nanoparticles; Bioconjugates; Raman effect